PENGEMBANGAN SENI DAN BUDAYA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM: KAJIAN PUSTAKA TERHADAP INTEGRASI NILAI ESTETIKA DAN RELIGIUSITAS DALAM PENDIDIKAN - Naura Zakia Ramadhani; Rif’ah Fitri Rahmawati; Risma Amelia Putri; Abdul Azis (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study discusses the role of art and culture in enriching the Islamic Religious Education (IRE) learning process through the integration of aesthetic and religious values. The research was conducted using a qualitative descriptive approach with a literature review method. Data were collected through an examination of various relevant literature sources, such as books, scientific journals, and previous research results discussing the relationship between art, culture, and Islamic education. The results of the study show that art and culture have an important contribution in shaping a more holistic, enjoyable, and meaningful learning experience. The integration of aesthetic values in PAI learning not only deepens students’ religious understanding but also fosters spiritual, social, and moral sensitivity. Through Islamic art activities such as calligraphy, religious music, and local cultural works, Islamic values can be internalized contextually and creatively. This study confirms that strengthening the aesthetic and cultural aspects of PAI learning is a strategic step in shaping the character of students who are religious, cultured, and noble in the midst of global modernization.